Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan Pada Batik Brotoseno Sragen - Nuryanti, Anis, Lukman Hakim, SE, M.Si (2016)
The purpose of this study were: 1) Determine whether the variable of organizational culture consisting of (innovation and risk taking, attention to detail things, oreintasi on results-orientated, people, team orientation, aggressiveness and stability) affect employee performance. 2) Determine which of the organization's culture consists of variables (innovation and risk taking, attention to detail things, oreintasi on results-orientated, people, team orientation, aggressiveness and stability) the most dominant influence. The population in this study were all employees Brotoseno Batik Sragen, while samples in this study were 30 respondents. The sampling technique by using purposive sampling or sampling based on the considerations and criteria. The analytical method used is: 1) test the research instrument, the validity and reliability testing, 2) test classic assumptions which include normality test, multicollinearity and heteroscedasticity test. 3) Test analysis covering multiple linear regression test, test the coefficient of determination (adjusted R2), F test and t test. The results of data analysis showed that: 1) Test instruments, all questionnaires declared valid and reliable. 2) Test the classical assumption, there is no error in the classic saumsi, 3) test results of data analysis showed that a) Results of regression analysis showed that the aggressiveness of the variables have the most influence on employee performance of the other variables. b) The test results coefficient of determination (adjusted R2) obtained at 0.987 or 98.7%, which means the cultural variables organizations able to explain variations in the variable employee performance by 98.7% and the remaining 1.3% is influenced by other variables outside this research model. c) F test results showed variable organizational culture consisting of innovation and risk taking, attention on the details, oreintasi on results-orientated, people-orientated, team, aggressiveness and stability together influential signifiakan the performance of employees in Brotoseno batik Sragen, this is shown by the significant value of less than 0.005. d) Results of t test showed that the variables of cultural organizations consisting of innovation and risk taking, attention on the details, oreintasi on results-orientated, people-orientated, team, aggressiveness and stability have a significant effect on the performance of employees this is indicated by the significance value of less than 0.005.